Implementation of Market Day Activities at SLB Bintang Harapan - Siti Fauziyah; Emay Mastiani (Universitas Pendidikan Mandalika, 2025)
Market Day is an educational activity designed to resemble a mini market, where students can sell their own work or products. This study aims to describe the implementation of the Market Day activity as a life skills learning strategy in Special Schools (SLB). The research was conducted using a qualitative descriptive method through observation, interviews, and documentation. The research subjects consisted of teachers in charge of the activity and students. The results showed that the Market Day activity was designed as part of contextual learning that emphasized the development of independence, social skills, and a basic understanding of economics. In the planning stage, teachers actively involved students in determining the types of products, division of tasks, and marketing strategies. During the implementation, students showed high enthusiasm and were able to carry out simple transactions, interact with buyers, and manage the money from sales. The activity was evaluated through joint reflection between teachers and students, which reinforced meaningful learning and encouraged the development of self-confidence. The Market Day activity proved to be an effective means of strengthening life skills and social integration for students with special needs. Thus, this activity can be recommended as a good practice of contextual learning in special needs schools, while also supporting the objectives of education for students with special needs. Keywords: Market Day, SLB, life skills, contextual learning, inclusive education Abstrak. Market Day adalah sebuah kegiatan edukatif yang dirancang menyerupai pasar mini, di mana peserta didik dapat menjual hasil karya atau produk buatan mereka sendiri. Penelitian ini bertujuan untuk mendeskripsikan implementasi kegiatan Market Day sebagai strategi pembelajaran keterampilan hidup di Sekolah Luar Biasa (SLB). Penelitian dilakukan dengan mengguanakan metode deskriptif kualitatif melalui observasi, wawancara, dan dokumentasi. Subjek penelitian terdiri dari guru penanggung jawab kegiatan dan peserta didik. Hasil penelitian menunjukkan bahwa kegiatan Market Day dirancang sebagai bagian dari pembelajaran kontekstual yang menekankan pada pengembangan kemandirian, keterampilan sosial, dan pemahaman dasar ekonomi. Dalam perencanaan, guru melibatkan peserta didik secara aktif dalam menentukan jenis produk, pembagian tugas, dan strategi pemasaran. Selama pelaksanaan, peserta didik menunjukkan antusiasme tinggi dan mampu melakukan transaksi sederhana, berinteraksi dengan pembeli, serta mengelola uang hasil penjualan. Evaluasi kegiatan dilakukan melalui refleksi bersama antara guru dan peserta didik, yang memperkuat pembelajaran bermakna dan mendorong perkembangan kepercayaan diri. Kegiatan Market Day terbukti menjadi sarana yang efektif dalam memperkuat keterampilan hidup dan integrasi sosial bagi peserta didik ABK. Dengan demikian, kegiatan ini dapat direkomendasikan sebagai salah satu praktik baik pembelajaran kontekstual di SLB, sekaligus mendukung tujuan Pendidikan untuk ABK. Kata kunci: Market Day, SLB, keterampilan hidup, pembelajaran kontekstual, pendidikan inklusif